TorakochirurgiaMalignant pleural mesothelioma – the progress in combined management - Krzakowski, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Malignant pleural mesothelioma has a very unfavourable prognosis due to the frequently advanced stage of disease. Histologically, there are 3 types of disease (epithelioid, sarcomatoid, and mixed) with different prognoses. Immunohistochemistry is essential to precisely diagnose and to differentiate malignant pleural mesothelioma from malignancies. Chest computed tomography is the primary imaging modality, whereas magnetic resonance imaging is used for final preoperative assessment. The current TNM staging system is based on the extent of local and lymph node involvement. Curative resections are performed in less than 10% of patients with unclear indications for radical interventions. The use of conventional radiotherapy is limited due to the risk of radiation-induced complications. Platinum compounds, doxorubicin, and several antifolates show modest activity in advanced disease. Given the natural course of malignant pleural mesothelioma and the relatively low effectiveness of single treatments, the multidisciplinary approach is promising. However, a combined approach should be provided in experienced institutions.